2018
DOI: 10.1182/blood-2018-01-778548
|View full text |Cite
|
Sign up to set email alerts
|

The management of Hodgkin lymphoma in adolescents and young adults: burden of disease or burden of choice?

Abstract: Adolescents and young adults (AYAs) comprise the largest age group affected by Hodgkin lymphoma (HL). Despite excellent overall survival of AYA patients with HL due to advances in treatment regimens, therapy-associated late effects continue to be a concern in HL survivors, especially for younger patients who have decades of life remaining. Since the first clinical trial for HL with chemotherapy in 1964, subsequent protocols have attempted to reduce chemotherapy-induced toxicities and yet maintain high overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…A study [12] involving 120 HL patients indicated that HBsAg prevalence was similar between HL patients and general population. In our study, compared with general population, cHL patients had similar HBsAg prevalence and lower anti-HBc prevalence, which may be due to routine childhood immunization in China [13] and domination of younger people in HL patients [14]. These findings suggested HBV infection may be not a pathogenesis factor for cHL.…”
Section: Discussionsupporting
confidence: 50%
“…A study [12] involving 120 HL patients indicated that HBsAg prevalence was similar between HL patients and general population. In our study, compared with general population, cHL patients had similar HBsAg prevalence and lower anti-HBc prevalence, which may be due to routine childhood immunization in China [13] and domination of younger people in HL patients [14]. These findings suggested HBV infection may be not a pathogenesis factor for cHL.…”
Section: Discussionsupporting
confidence: 50%
“…Due to improvements in the treatment and prognosis of cancer, the number of cancer survivors has increased (1). "Childhood cancer survivors (CCS)" and "adolescent and young adult (AYA) cancer survivors" are known to be at risk of various complications, e.g., second cancer, cardiovascular, endocrine, pulmonary, or neurological problems (2)(3)(4)(5)(6). The Long-Term Follow-Up Guidelines for Survivors of Childhood, Adolescent, and Young Adult Cancers, issued by the Children's Oncology Group, are recognized as very useful resources for healthcare providers (7).…”
Section: Introductionmentioning
confidence: 99%
“…Following patients over the last several decades allowed us to recognize the long-term health effects of curative therapeutic approaches, and subsequently long-term follow-up is essential to avoid trading one toxicity for another. Harmonization efforts for supportive care and long-term follow-up recommendations are underway and will be beneficial to provide therapy-specific and risk-adapted monitoring for toxicities and effects of therapy (2,6,70,(72)(73)(74). Ehrhardt makes a compelling argument to assess and consider the risk of late toxicities, converting this risk assessment into actionable data for the choice of upfront therapy (6).…”
Section: Discussionmentioning
confidence: 99%